Skin substitutes as treatment for chronic wounds: current and future directions - Vecin, Nicole M.; Kirsner, Robert S. (Frontiers in Medicine, 2023)
Chronic wounds such as diabetic foot ulcers and venous leg ulcers place a significant burden on the healthcare system and in some cases, have 5-year mortality rates comparable to cancer. They negatively impact patients’ quality of life due to pain, odor, decreased mobility, and social isolation. Skin substitutes are an advanced therapy recommended for wounds that fail to show decrease in size with standard care. The choice of substitute used should be based on evidence, which often differs based on wound etiology. There are more than 75 skin substitutes currently available, and that number is rising. In this review, we discuss current management and future directions of chronic wounds while providing a review of available randomized control trial data for various skin substitutes.